Small photovoltaic setup for the air conditioning system - Masiukiewicz Maciej (E3S Web of Conferences, 2017)
The increasing interest in air conditioning systems for residential applications in Poland will certainly increase the demand for electricity during the summer period. Due to this fact a growing interest in solutions that help to lower the electricity consumption in this sector is observed. The problem of increased energy demand for air conditioning purposes can be solved by transfer the consumption of electricity from the grid system to renewable energy sources (RES). The greatest demand for cooling occurs during the biggest sunlight. This is the basis for the analysis of technical power system based on photovoltaic cells (PV) to power the split type air conditioner. The object of the study was the commercial residential airconditioning inverter units with a capacity of 2.5kW. A network electricity production system for their own use with the possibility of buffering energy in batteries (OFF-GRID system). Currently, on the Polish market, there are no developed complete solutions dedicated to air conditioning systems based on PV. In Poland, solar energy is mainly used for heat production in solar collectors. The proposed solution will help to increase the popularity of PV systems in the Polish market as an alternative to other RES. The basic conclusion is that the amount of PV energy generated was sufficient to cover the daily energy requirement of the air conditioner.